PENGEMBANGAN MEDIA ENERGY.EDU BERBANTUAN SCRATCH BERBASIS MODEL CHILDREN LEARNING IN SCIENCE (CLIS) UNTUK MENINGKATKAN KETERAMPILAN PROSES SAINS SISWA SEKOLAH DASAR - Hanifah Tri Nur Fadillah; Fitri Nuraeni; Tiara Yogiarni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Energy.edu is a digital learning media developed as a solution to the low level of students science process skills, especially on Energi yang Bergerak topics. This research aims to develop scratch-assisted energy.edu media based on the Children Learning in Science (CLIS) model to improve elementary school students' science process skills.. This research method utilizes Research and Development (R&D) in conjunction with the Analysis, Design, Development, Implementation, and Evaluation (ADDIE) model. The research sample consisted of 25 experimental class students and 25 control class students in class IV at SDN 1 Munjuljaya. The results showed that the energy.edu media that had passed the product test stage by media experts received a score of 85% with very feasible criteria. Energy.edu is also able to improve KPS better than conventional learning; this can be proven from the comparison of pre-test and post-test results per indicator of science process skills that increase. In addition, energy.edu media also has an effect of using the CLIS model on KPS by 49%. Energy.edu is expected to be an alternative solution in improving students' science process skills on the topic of moving energy, and is recommended to be widely used to utilize technology in teaching media and maximize IPAS learning.